Profitabilitas Perusahaan Perkebunan Kelapa Sawit: Studi Literatur Modal Kerja, Likuiditas, Struktur Modal, dan Ukuran Perusahaan - Dedy Gurning; Yusniar Lubis; Ahmad Rafiki; Utari Azrani; Muhammad Reza Aulia (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Profitability is a central indicator of corporate performance in palm oil plantation companies because the industry is capital intensive, relies on biological assets, and faces commodity price volatility. This article develops a narrative literature review of working capital management, liquidity, capital structure, and firm size in explaining profitability. The review synthesizes books, review articles, and previous empirical studies on cash turnover, receivables turnover, inventory turnover, current ratio, debt to equity ratio, and firm size. The synthesis indicates that working capital components should be interpreted as operational mechanisms rather than isolated ratios: cash secures operating continuity, receivables represent credit quality and collection efficiency, inventory reflects stock optimization, liquidity balances short-term safety and asset productivity, and capital structure reflects the cost-benefit trade-off of debt. Firm size is positioned as a contextual factor that can strengthen or weaken financial policy effectiveness. This article provides a conceptual framework for future empirical studies without presenting statistical results from company data. The synthesis offers practical guidance for financial managers in palm oil companies to determine an optimal working-capital buffer, accelerate receivables collection, align inventory levels with harvesting and processing cycles, and maintain liquidity without sacrificing asset productivity. Debt and financing decisions should also be aligned with operating cash-flow capacity and firm scale to safeguard profitability amid commodity-price fluctuations.